Enlightening behavioral disturbances in myotonic dystrophy type 1 through neuropsychology and imaging correlations: Insights from the frontal and temporal lobe functions: Neuropsychiatry and behavioral neurology/presymptomatic disease/prodromal disease/prodromal states. (7th December 2020) - Morin, Alexandre; Funkiewiez, Aurélie; Routier, Alexandre; Colliot, Olivier; Eymard, Bruno; Dubois, Bruno; Stojkovic, Tanja; Azuar, Carole
Abstract: Background: Myotonic Dystrophy Type 1 (MD1) is a neuromuscular disease in which subtle behavioral disturbance is often described. Few studies evaluated frontal lobe function and behavioral scales in relation with brain pathology. Method: 27 MD1 adult patients (mean age 46), were included. All patients performed an exhaustive neuropsychological assessment with a specific focus on cognitive and behavioral frontal functions. 18 MD1 patients and 18 healthy controls had a brain MRI with T1 and T2 Flair sequences. We performed a voxel‐based analysis with SPM12 via Clinica Software. The normalized data were smoothed with an isotropic Gaussian kernel of 8 mm. Statistical analysis was performed using general linear model with age sex and total intra cranial volume as covariates. Statistics were corrected for multiple comparisons with family‐wise error (FWE) correction at the cluster level with a height threshold of 0.001. T2 white matter lesions were segmented with VolBrain software. Result: More than 60 % of the patients showed significant impairment in executive frontal functions (inhibition, mental flexibility, contextualization and theory of mind) with relative sparing of motivation, emotion recognition and initiation/planification. MD1 patients MRI compared to healthy controls showed grey matter atrophy in medial temporal lobe, (parahippocampus mostly) and in a smaller extent in the middle frontal gyrus and the right caudate nucleus and excessive white matter hyperintensities, mostly in temporal lobes. Frontal cognitive and behavioral impairment on neuropsychological testing was correlated with medial temporal and in a smaller extent frontal localization. Conclusion: Behavioral disturbance in MD1 might be related to cognitive impairment in mental flexibility and contextualization rather than a specific social cognition deficit. This impairment might be related to white matter lesions or grey matter disease (including frontal‐subcortical network or parahippocampus, known to apprehend contextualization in emotion detection). Altogether, these findings confirm the hypothesis of a specific central nervous system involvement in MD1 patients.